2013
DOI: 10.1099/ijs.0.041467-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Phytoplasma malaysianum’, a novel taxon associated with virescence and phyllody of Madagascar periwinkle (Catharanthus roseus)

Abstract: This study addressed the taxonomic position and group classification of a phytoplasma responsible for virescence and phyllody symptoms in naturally diseased Madagascar periwinkle plants in western Malaysia. Unique regions in the 16S rRNA gene from the Malaysian periwinkle virescence (MaPV) phytoplasma distinguished the phytoplasma from all previously described 'Candidatus Phytoplasma' species. Pairwise sequence similarity scores, calculated through alignment of full-length 16S rRNA gene sequences, revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 63 publications
0
37
0
2
Order By: Relevance
“…So far, 32 16Sr groups have been formally described, which are generally associated with the description of novel candidate species of 'Ca. Phytoplasma' Lee et al, 2011;Nejat et al, 2013). In this study, two novel 16Sr groups were identified from previous reports.…”
Section: New Groups 16srxxxiii and 16srxxxivmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, 32 16Sr groups have been formally described, which are generally associated with the description of novel candidate species of 'Ca. Phytoplasma' Lee et al, 2011;Nejat et al, 2013). In this study, two novel 16Sr groups were identified from previous reports.…”
Section: New Groups 16srxxxiii and 16srxxxivmentioning
confidence: 99%
“…In 1993, the first 16S rRNA RFLP (16Sr) group was delineated (Lee et al, 1993) and, in 2009, Zhao and colleagues reported the existence of 29 16Sr groups designated 16SrI-16SrXXIX . Recently, this has been expanded to include groups up to 16SrXXXII (Nejat et al, 2013), highlighting the vast diversity among phytoplasmas strains worldwide. The development and validation of computer-simulated RFLP analysis, along with an automated RFLP patterncomparison program that facilitates the calculation of similarity coefficients for differentiating phytoplasma groups/ subgroups, was an important advancement in the field of phytoplasma characterization (Wei et al, 2007(Wei et al, , 2008b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En la actualidad existen dos sistemas paralelos de clasificación, ambos basados en el gen 16SrDNA. El primero establece los grupos a partir de patrones de corte de 17 enzimas de restricción en 32 grupos 16Sr RNA (Nejat et al, 2013). A su vez, cada grupo puede estar subdividido en subgrupos cuya determinación se complementa usando secuencias de otros genes como rp (proteínas ribosomales), secY, tuf y la región intergénica espaciadora 16S-23SrDNA, entre otros (Smart et al, 1996;Martini et al, 2007;.…”
Section: Introductionunclassified
“…Phytoplasma' species have been formally described based on 16S rRNA gene sequence phylogeny and/or biological/phytopathological characteristics (Firrao et al, 2004;Harrison et al, 2014). Based on their identification and classification by RFLP analysis of 16S rRNA gene sequences, 32 phytoplasma/16Sr groups and more than 100 subgroups have been identified (Lee et al, 1993(Lee et al, , 1998Nejat et al, 2013).…”
mentioning
confidence: 99%